Clinical analysis of 26 patients with histologically proven placental chorioangiomas. (April 2016) - Wu, Zaigui; Hu, Wensheng
Abstract: Objectives: The purpose of this study was to evaluate the clinical characteristics, imaging features, pregnancy complications, prenatal management of patients with placenta chorioangioma. Methods: This was a retrospective study of 26 cases with histologically proven placenta chorioangima, in which the natural history, pregnancy complications, and clinical characteristics including ultrasonography were evaluated. Results: Twelve of the twenty-six cases had a wide range of maternal–fetal complications including polyhydramnios (7), fetal growth restriction (3), fetal distress (2), pre-eclampsia (3), fetal anemia-thrombocytopenia (2), congestive heart failure (1) and fetal abnormality (1). Conclusions: Placenta chorioangioma was associated with series of pregnancy complications such as polyhytramnios, premature delivery, maternal pre-eclampsia, fetal growth restriction, fetal distress, even fetal anemia and cardiomegaly. With regular prenatal examination, necessary treatment, and timely delivery, the majority had a good pregnancy outcome.